Reported happiness, fast and slow - Raphael Studer; Rainer Winkelmann (University of Zurich, Department of Economics, 2012)
In this paper, we test how reporting behaviors (response time, cognitive effort, questionnaire order) affect reported happiness in a large Dutch internet panel survey. We find that slower responses and higher cognitive effort reduce reported happiness. Moreover, in multivariate happiness equations, these factors moderate the estimated effect of income on happiness, while no interaction effects are found for other determinants of happiness. As a consequence, relative marginal effects may not be invariant to reporting circumstances.
Keywords: I31; 330; reporting function; happiness; mood; Zufriedenheit; Messung; Bias; Panel; Niederlande